The transition in the ventral stream from feature to real-world entity representations - Orban, Guy A.; Zhu, Qi; Vanduffel, Wim (Frontiers in Psychology, 2014)
We propose that the ventral visual pathway of human and non-human primates is organized into three levels: 1) ventral retinotopic cortex including what is known as TEO in the monkey but corresponds to V4A and PITd/v, and the phPIT cluster in humans, 2) area TE in the monkey and its homologue LOC and neighboring fusiform regions, and more speculatively, 3) TGv in the monkey and its possible human equivalent, the temporal pole. We attribute to these levels the visual representations of features, partial real-world entities (RWEs), and known, complete RWEs, respectively. Furthermore, we propose that the middle level, TE and its homologue, is organized into three parallel substreams, lower bank STS, dorsal convexity of TE and ventral convexity of TE, as are their corresponding human regions. These presumably process shape in depth, 2D shape and material properties, respectively, to construct RWE representations.